An Enhanced Feedback-Base Downlink Packet Scheduling Algorithm for Mobile TV in WIMAX Networks - Joseph Oyewale; Liu Xiao Juan (International Journal of Science and Engineering, 2013)
With high speed access network technology like WIMAX, there is the need for efficient management of radio resources where the throughput and Qos requirements for Multicasting Broadcasting Services (MBS) for example TV are to be met. An enhanced  feedback-base downlink Packet scheduling algorithm  that can be used in IEEE 802.16d/e networks for mobile TV “one way traffic”(MBS) is needed to support many users utilizing multiuser diversity of the  broadband of WIMAX systems where a group of users(good/worst channels) share allocated resources (bandwidth). This paper proposes a WIMAX framework feedback-base (like a channel-awareness) downlink packet scheduling algorithm for Mobile TV traffics in IEEE806.16, in which network Physical Timing Slots (PSs) resource blocks are allocated in a dynamic way to mobile TV subscribers based on the Channel State information (CSI) feedback, and then considering users with worst channels with the aim of improving system throughput while system coverage is being guaranteed. The algorithm was examined by changing the PSs bandwidth allocation of the users and different number of users of a cell. Simulation results show our proposed algorithm performed better than other algorithms (blind algorithms) in terms of improvement in system throughput performance. Doi: 10.12777/ijse.5.1.55-62 [How to cite this article: Oyewale, J. and , Juan, L.X.. (2013). An Enhanced Feedback-Base Downlink Packet Scheduling Algorithm for Mobile TV in WIMAX Networks. International Journal of Science and Engineering, 5(1),55-62. Doi: 10.12777/ijse.5.1.55-62]